The Role of Organizational Culture Adaptation and Job Satisfaction in Mediating Effects of Human Resource Flexibility on Employee Performance - Sabuhari, Rahmat (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2021)
This research aims to analyze the direct effect of human resource flexibility, organizational culture adaptation, and job satisfaction on employee performance, and also the indirect influence between human resource flexibility on employee performance through organizational culture adaptation and the effect of organizational culture adaptation on employee performance through job satisfaction. The method of data collection is a survey using a questionnaire. The sampling technique used sampling with certain criteria and obtained 153 samples from 176 respondents that could be analyzed. The results showed that there was a positive and significant influence between the HR flexibility and employee performance, job satisfaction and employee performance, but organizational culture adaptation did not have a significant effect on employee performance, this also resulted in organizational cultural adaptation unable to mediate the effect of HR flexibility on employee performance. Job satisfaction is also able to mediate the influence of organizational culture adaptation on employee performance. HR flexibility and job satisfaction provide a very significant role in improving employee performance.